Qualitative Research In Organizational Studies (EOR): Mapping of Methodological Choices (Management and Connections Journal, 2024)
This work aims to expand the dialogue with organizational researchers by presenting qualitative approaches of Brazilian Organizational Studies (OS), in order to allow on choices and methodological strategies. The most used traditional methods and their consequences stand out: Case Study, Ethnography, Oral and Life History, Action Research and Grounded theory. Aspects related to the approaches discussed are presented, mainly to compliance with rigor and relevance, considering their variations, limitations and potential for carrying out different qualitative studies. Qualitative research in EOR is a free and open field and, therefore, should be better studied by organizational researchers; and the diversity of qualitative strategies in the organizational field requires reflexivity on the part of researchers, thus making it necessary for research  to be conducted and produced with rigor so that they can impact qualitative research in the EOR.